Socioeconomic and cultural factors associated with mortality in Malaria induced anaemia among under-five children in Benin city, Nigeria - Abhulimhen-Iyoha, Blessing Imuetinyan; Israel-Aina, Yetunde Tinuola (Bangladesh Journal of Medical Science, 2014)
Background: Children under the age of five years bear the brunt of malaria infection. Malaria induced anaemia (MIA) is the most prevalent presentation of malaria and a major cause of morbidity and mortality in Nigeria. Objective: To determine the socioeconomic and cultural factors associated with mortality in under-five children presenting with malaria induced anaemia. Methods: This is a cross-sectional descriptive study conducted at the Children Emergency Room of the University of Benin Teaching Hospital, Benin City, Nigeria. Questionnaires which were researcher-administered were used to collect information on the childs age, gender, parents or caregivers education, occupation, recognition of symptoms of malaria and anaemia, cultural practices during childs illness and patients outcome. Results: The case fatality rate was 3.1%. Poor parental education, low social class and lack of skilled job amongst the parents were associated with high mortality. Other factors associated with mortality include high patronage of chemists and prayer houses as well as poor recognition of pallor by mothers. Conclusion/Recommendations: Improvement in socioeconomic status especially female education and empowerment is again emphasized. This and other socioeconomic boost should be targeted alongside malaria-control programmes in order to reduce mortality associated with malaria induced anaemia. Parental enlightenment on recognition of symptoms of malaria and anaemia will improve their health-seeking behaviour, promote early diagnosis and prompt institution of effective antimalarial therapy. DOI: http://dx.doi.org/10.3329/bjms.v14i1.17274 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.32-38